Enhancing pronunciation skills through British Council Podcasts: Learners’ beliefs and learning experiences - Sukarni, Semi; Sudar, Sudar; Vezner, Irina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study investigates the implementation of British Council Podcasts to enhance pronunciation skills and explores learners' beliefs regarding this pedagogical tool. Employing a Classroom Action Research (CAR) design comprising planning, acting, observing, and reflecting phases, the research involved 27 first-semester students of the English Language Education Department at Purworejo Muhammadiyah University. Data were collected through pronunciation tests, observations, and questionnaires. Quantitative data were analyzed using descriptive statistics, while qualitative data from observations were analyzed thematically. The findings indicate a notable improvement in students' pronunciation skills, with the mean score increasing from 68.4 in Cycle 1 to 76.8 in Cycle 2. Furthermore, questionnaire results revealed a high mean score of 3.95, indicating that students hold positive beliefs about using podcasts for pronunciation learning. In conclusion, British Council Podcasts are an effective and positively perceived medium for enhancing pronunciation skills among EFL learners.